A Review on the Tribological Performances of High‐Entropy Alloys. Issue 8 (9th February 2022) - Wu, Jian; Chen, Yujie; Zhu, Heguo
Abstract : Wear is an important form of material loss and failure, and it is usually inevitable in almost all mechanical systems with moving parts. The durability and reliability of engineering components are closely related to their wear resistance. Developing advanced materials to alleviate energy and materials losses in moving mechanical systems still remains a great challenge nowadays. The emergence of novel high‐entropy alloys (HEAs) that compose of multiple principal elements holds great promise for the development of materials with extraordinary wear resistance, due to their high hardness, high wear resistance, and excellent corrosion resistance. Herein, the current research progress of the tribology of HEAs under different conditions is reviewed, including high temperature, dry condition, corrosion solution, and oil lubrication. Specifically, the effects of compositions, microstructures, lubricants, and protective oxide layers on the tribological performance of HEAs are summarized. Furthermore, the underlying mechanisms that are responsible for the excellent wear resistance of HEAs under different conditions are discussed. Finally, the current challenges and the future outlooks are emphasized and addressed systematically. In view of the excellent tribological performances and the diversity of compositional design, HEAs have great potential to be applied in a wide range of mechanical systems to minimize wear. Abstract : The emergence of high‐entropy alloys holds great promise for the development of materials with extraordinary wear‐resistance. The current research progress of the tribology of HEAs under different conditions are reviewed, including high temperature, dry condition, corrosion solution and oil lubrication. Furthermore, the underlying mechanisms that are responsible for the excellent wear resistance of HEAs under different conditions are discussed.